The inverse microconglomerate test: Further evidence for the preservation of Hadean magnetizations in metasediments of the Jack Hills, Western Australia. Issue 9 (4th May 2016) - Cottrell, Rory D.; Tarduno, John A.; Bono, Richard K.; Dare, Matthew S.; Mitra, Gautam
Abstract: We introduce a new paleomagnetic test, applicable to metamorphosed terrains, that assesses the recording fidelity of a metasediment. Magnetic mineral carriers with unblocking temperatures lower than the peak metamorphic temperature should record a common remagnetization direction, whereas those with higher unblocking temperatures should be randomly distributed if a primary magnetization has been preserved on a sedimentary grain scale. We call this an inverse microconglomerate test. Application to metasediments of the Jack Hills (JH), Western Australia, reveals that the chrome mica fuchsite records a well‐grouped secondary magnetization at unblocking temperatures between ∼270 and 340°C, in contrast to the random distribution of in situ directions held by zircons isolated at unblocking temperatures >550°C. This positive test further supports JH zircons as hosts of primary Hadean magnetizations. More generally, the new test can aid in understanding the timing of peak metamorphism and deformation in complex terrains. Key Points: A new paleomagnetic field test, the inverse microconglomerate test, is introduced The test further supports zircons as recorders of primary Hadean magnetizations The new test can assist in relating peak metamorphism to deformation